A 60‐GHz variable gain amplifier with low phase and OP1dB variation. Issue 2 (30th October 2019) - Byeon, Chul Woo; Park, Chul Soon
Abstract: This article presents a 60 GHz variable gain amplifier (VGA) with a low phase and output 1‐dB gain compression point (OP1dB) variation for phased‐array applications. The VGA employs a two‐stage modified current‐steering cascode. Implemented in 0.18‐μm SiGe BiCMOS technology, the VGA has a gain control range of 20.4 dB with a maximum gain of 17.7 dB at 60 GHz. The OP1dB variation is only 2.3 dB for all gain states at 60 GHz with a DC power consumption of 50 mW, and the measured phase variation is less than 4.8° at 57 to 66 GHz.